Garage Sales: Meaning and Messages of Material Culture - Maxwell, Mary Percival; Maxwell, James D. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1993)
Focusing on the phenomenon of the garage sale and the cultural meaning of this type of consumer behaviour, the argument is made in a semiotic framework that the meaning of an object, what it ’signs’, is conditioned by the mode of organization in which it is located. The garage sale itself represents part of the System of redistribution of consumer goods within the hidden economy, but more importantly, like the items themselves, the sales represent a new way of constituting meaning and identity which differe considerably from the usual patterns of consumerism found in modem capitalism.